Halogen Bonding: Halogen‐Bond Mediated 3D Confined Assembly of AB Diblock Copolymer and C Homopolymer Blends (Small 18/2021). Issue 18 (6th May 2021) - Zheng, Xihuang; Ren, Min; Wang, Huayang; Wang, Huiying; Geng, Zhen; Xu, Jiangping; Deng, Renhua; Chen, Senbin; Binder, Wolfgang H.; Zhu, Jintao
Abstract : Halogen‐bond mediated 3D confined assembly gives rise to a profound picture of morphological transition when combining with polymer donor‐acceptor pairs, changing from spherical to cylindrical, lamellar, and then to inverse cylindrical structures, by tuning the feeding ratio and choice of surfactant (presented by Senbin Chen, Wolfgang H. Binder, Jintao Zhu, and co‐workers in article number 2007570 ). Subsequent selective swelling/deswelling triggers the formation of mesoporous microparticles, disassembled nanodiscs, and superaggregates.